Covid-19 Vaccination During Pregnancy and First-trimester Miscarriage. Issue 3 (24th September 2022) - Magnus, M.C.; Gjessing, H.K.; Eide, H.N.; Wilcox, A.J.; Fell, D.B.; Håberg, S.E.
Abstract : ( N Engl J Med . 2021;385:2008–2010. [Epub October 20, 2021]) Parturient women are encouraged to receive the COVID-19 vaccination to decrease adverse maternal outcomes, however, vaccination safety data during pregnancy is limited.